How the actual Comments of "Carta sings" from Palma! - Ward, Thomas (2020)
Peruvian author Ricardo Palma achieved prominence as a South American literary through his pleasant and entertaining Peruvian Traditions that mostly resurrected the colonial world. To write his historical fiction, Palma was inspired by the Chronicles of the Indies and the plot of his tradition “Carta canta” comes directly from Inca Garcilaso de la Vega’s Royal Commentaries. However, from the firstincarnation of the tradition from 1875 to the last one, Palma conceals his true source of the story. For the second version, improved after the War of the Pacific, our philological research reveals that Palma continued tweaking still other Garcilaso elements. We offer some conclusions about why he insisted on hiding his debt to Garcilaso and what coloniality had to do with his motivations.